1982
DOI: 10.1021/ac00240a004
|View full text |Cite
|
Sign up to set email alerts
|

Tungstic acid for preconcentration and determination of gaseous and particulate ammonia and nitric acid in ambient air

Abstract: Tungstic acid surfaces chemisorb NH, and HNOa. Coilectlon of these gases is posslbie by sampling with a hollow tube, the interior of which is coated wlth tungstic acid. Under conditions of laminar flow, the gases diffuse to the wail and are chemisorbed while particles are carried through the tube. Particles are collected with an in-line tube packed with tungstic acid coated sand. Thermal desorption followed by a simple separation and detection by a chemiluminescent NO, analyzer permits analyses at the parts pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
3
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 19 publications
6
52
3
2
Order By: Relevance
“…The HNO 3 diffusion coefficient in air was experimentally determined by several investigators ranging from 0.04 cm 2 s −1 to 0.121 cm 2 s −1 (STP) (Braman et al, 1982;Eatough et al, 1985;Durham and Stockburger, 1986;and Deandrade et al, 1992). In this study, we used the highest value (0.121 cm 2 s −1 ).…”
Section: Sampling Efficiency Of the Inlet Systemmentioning
confidence: 99%
“…The HNO 3 diffusion coefficient in air was experimentally determined by several investigators ranging from 0.04 cm 2 s −1 to 0.121 cm 2 s −1 (STP) (Braman et al, 1982;Eatough et al, 1985;Durham and Stockburger, 1986;and Deandrade et al, 1992). In this study, we used the highest value (0.121 cm 2 s −1 ).…”
Section: Sampling Efficiency Of the Inlet Systemmentioning
confidence: 99%
“…The interaction of trace gases with surfaces, and therefore gas phase diffusion coefficients, are not only important in the investigation of atmospheric heterogeneous reactions, but are also important to describe the efficiency of diffusion denuders which are widely used to collect trace gases or to separate trace gases from aerosol particles. For example, denuder tubes in which inner walls are coated with adsorbents are widely used to capture trace gases such as HNO 3 (Braman et al, 1982;Durham et al, 1987;Eatough et al, 1985), HONO (Ferm and Sjodin, 1985) and NH 3 (Braman et al, 1982) for online/offline analysis, and to separate aerosol particles from gases (e.g. to separate NH 3 from particulate NH + 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The HNO3 diffusion coefficient value used (0.12 cm 2 /s) was calculated by the method of Wilke and Lee. 10 Braman et al 4 found experimentally an approximating value and Ferm 3 a value of 0.116 cm 2 /s. The denuder preparation could be reproduced.…”
Section: Results Anddiscussionmentioning
confidence: 96%
“…A denuder chosen for such a system should have a chemically stable coating with respect to regeneration and collection during ambient sampling runs to avoid frequent calibration of the system. The in situ monitoring of ambient HNO3 (and NH3) concentrations with a denuder system was described by Braman et al 4 and adapted to automatic operation.…”
mentioning
confidence: 99%